(untitled) (Marketing Journal, 2025)
This paper discusses the main directions for improving product quality in manufacturing enterprises and its impact on competitiveness. The role of quality control and management systems in modern production, the importance of 57 implementing innovative technologies, and improving the qualifications of employees to ensure that products meet consumer demands are analyzed. Additionally, the ways of forming a healthy competitive environment, applying free market principles, and achiev ing economic growth through effective competition among enterprises are explored. It is justified that the synergy of product quality and a competitive environment in the production sector contributes to the sustainable development of enterprises and enhan ces their opportunities for entering international markets.